The use of modern management accounting systems for continuous improve the performance of Jordanian Industrial Companies - الشيخ, عماد يوسف (Journal of Economics and Administrative Sciences, 2015)
The intensification of competition among all companies and at different levels has become necessary for every company need to continue to improve its performance in order to be able to face the competition and stay in the market. To achieve this, we must rely on the company's accounting information more accurate and appropriate and provided in a timely manner, for the purpose of use in planning and decision making.So there must be information systems that help the administration to continuous development and improvement of the performance of companies in general, and this is what you need Jordanian companies, especially after the accession of Jordan to the field of economy. The management system was selected on the basis of the activities and the system of budgets prepared on the basis of the activities as tools for continuous improvement and development of the performance of industrial companies listed Jordanian public shareholding in the Amman Financial Market (Amman Stock Exchange of Finance).        Perhaps the most important findings of the study is that the industrial companies Jordanian public shareholding has the basic components needed to implement each of the budgets and management systems on the basis of activities, as have the systems to help implement a systematic management of budgets and buildings on the basis of the activities. But they do not have a cadre who has a sufficiently familiar with budgets and management systems on the activity based built, and most of the departments of industrial companies Jordanian public shareholding was convinced of the benefits of the management system based on the most active